Fatores que interferem na comunicação conjulgal e suas repercussões na família - Silva Filho, Francisco Dias da (2012)
This research investigated the factors that interfere in marital communication and its family repercussions. It is known that communication problems stand in marital relationships and cause difficulties not only for the couple but also for the children and the living of them before society. This is marked as a qualitative research which had as participants, 07 (seven) families constituted of heterosexual couples who live together for more than five years, have children and are considered lower-income people and they already had or they are still facing crises in their relationship. The researched families had an average of two children aged between 03 and 16 years old. The average ages of the spouses ranged from 31 to 43 years old and the marital living reached 12 years and two months long. The instruments used were: a Semi-Structured Interview and the Structured Family Interview (EFE) of Terezinha Féres- Carneiro (2005). To collect the obtained material we filmed and we recorded the participants' speeches; it was also used the Technique of Thematic Content Analysis. The analysis of the EFE was made based on the indicators themselves already validated in Brazil. Results showed that all couples started a relationship because of an unexpected pregnancy before the exercise of conjugality which served as a predictor of communication difficulties from the start of marital living. Couples surveyed and their families currently face difficulties because of financial problems, interference from background family, lack of individualization, poor housing conditions, difficulties on interpretation of communication from the spouse which has directly affected their children and the social environment in which they live in. According to data obtained through this research, it is confirmed the relevance of studies on marital communication in marital relationship and the need to support and sponsor more systematic studies into this area in order to subsidize psychology professionals and the several areas which work with couples and family such as: churches, community associations and government programs directed toward this purpose, such as the Program of Family Health - PSF